2013
DOI: 10.1007/s10903-013-9959-5
|View full text |Cite
|
Sign up to set email alerts
|

Family Cohesion Moderates the Relationship between Acculturative Stress and Depression in Japanese Adolescent Temporary Residents

Abstract: Acculturative stress is a risk factor for depression, and may be important in the risk for depression among acculturating Japanese adolescents. However, little to no research has been published on the mental health of acculturating Japanese adolescents. Further, although family cohesion has been shown to be protective against depression across ethnic groups, no prior research has examined family cohesion as a protective factor for Japanese adolescents. To examine these relationships, 26 Japanese temporary resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Thirty-seven (45%, 37/81) studies were original, independent studies, while forty-four (54%, 44/81) consisted of secondary analyses of national surveys. Only considering Asian American adolescents and not comparisons or parent groups, the sample size among independent studies ranged from 26 [ 38 ] to 451 [ 39 ] adolescents. Among studies conducting secondary analysis of national surveys, the sample size ranged from 84 [ 40 ] to 1664 [ 41 ] adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-seven (45%, 37/81) studies were original, independent studies, while forty-four (54%, 44/81) consisted of secondary analyses of national surveys. Only considering Asian American adolescents and not comparisons or parent groups, the sample size among independent studies ranged from 26 [ 38 ] to 451 [ 39 ] adolescents. Among studies conducting secondary analysis of national surveys, the sample size ranged from 84 [ 40 ] to 1664 [ 41 ] adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Acculturative stress refers to the negative psychological impact of this process [ 57 ]. A total of thirteen (16%, 13/81) studies addressed the influence of acculturative stress, or related factors such as length of stay and acculturative coping mechanisms, on depressive symptoms [ 33 , 38 , 43 , 47 , 49 , 51 , 57 , 61 , 62 , 70 , 71 , 72 , 73 ]. Of these, six (7.4%, 6/81) studies consistently found that acculturative stress was related to greater reporting of depressive symptoms, particularly low self-esteem and somatic symptoms [ 33 , 38 , 43 , 49 , 57 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Roley et al. (2014) found that Japanese immigrant youth in the United States who felt supported by and connected to their families were less at risk for developing depression even when experiencing higher levels of acculturative stress.…”
Section: Family Cohesionmentioning
confidence: 99%
“…Like many Asian cultures, Chinese culture prioritizes the value of family and, therefore, members seek family support when facing stressful life events like migration (Salant & Lauderdale, 2003). While it is among the most important protective factors of health for Chinese Americans (Park et al, 2014), family cohesion, defined as “the emotional bonding that family members have toward one another” (Olson et al, 1979), has received inadequate attention in the context of understanding the relationship between acculturation and self-rated health (Roley et al, 2014). According to Hobfoll et al’s (1990) conservation of resources theory, losing resources in one area, for example, migrating or acculturating to a different culture, may trigger individuals’ investment in other resource areas, for example, family support, to maintain their well-being.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%